2017
DOI: 10.1080/09593330.2017.1397763
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of Moringa oleifera’s polymer blends

Abstract: Vegetable oils are used as a base for the synthesis of polymers and monomers with structures similar to that of petroleum, as plasticizers for conventional polymers and biodegrading additives. The Moringa oleifera oil was extracted from seeds and polymerized after being submitted to 16 h of microwave irradiation without catalysers. This polymer was characterized and the efficiency of the oil polymerization was verified by the reduction of double bonds and the increase of molecular weight up to 50,000 g mol. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…The third event occurs from 300 to 428 °C, which corresponds to the PMO. This study was like the previous studies by Finzi-Quintão et al 78 The SAF shows some similar degradation properties, and the samples almost overlapped the profile relating to that of pure sodium alginate powders, except for the presence of an additional decomposition step, the details, show the first stage occurring at the same temperature of 40–110 °C temperature while the losses are positioned at a temperature of 330–350 °C. The degradation step can tentatively be ascribed to the crosslinking degradation property step of SA as reported by Pan et al 79 which stabilizes the polymer and consequently delays its degradation.…”
Section: Resultssupporting
confidence: 88%
“…The third event occurs from 300 to 428 °C, which corresponds to the PMO. This study was like the previous studies by Finzi-Quintão et al 78 The SAF shows some similar degradation properties, and the samples almost overlapped the profile relating to that of pure sodium alginate powders, except for the presence of an additional decomposition step, the details, show the first stage occurring at the same temperature of 40–110 °C temperature while the losses are positioned at a temperature of 330–350 °C. The degradation step can tentatively be ascribed to the crosslinking degradation property step of SA as reported by Pan et al 79 which stabilizes the polymer and consequently delays its degradation.…”
Section: Resultssupporting
confidence: 88%
“…In 2018, Finzi-Quintao et al reported a comparative study of Moringa oleifera oil in mixtures with commercial polymers [12]. Furthermore, Finzi-Quintao et al suggested another study in 2019 concerned with the biodegradation of Moringa oleifera's polymer blends [13]. In 2016, Abd-Rabou et al addressed and explored the potential of Moringa oleifera seed oil as an impact compound to promote the mechanism of mitochondrial apoptosis of cancer cell death [14].…”
Section: Introductionmentioning
confidence: 99%